Pengaruh Direct Marketing Dan Product Quality Terhadap Minat Beli Pada Live Streaming Marketing Online Shop - Mefri Yudi Wisra,; Mulyadi Mulyadi,; Indra Nara ,; Febri Edward, (Manajemen Kreatif Jurnal, 2023)
The development of increasingly sophisticated technology has an impact on various fields. One of the impacts of technological developments is social media. Many business people are utilizing social media as an e-commerce business platform by presenting innovative features and programs to help them compete in the market. To attract attention and increase consumer satisfaction, most e-commerce providers use live streaming. This allows buying and selling activities in real-time and reduces consumer concerns about the quality of the products offered. The purpose of this study is to analyze the effect of direct marketing and product quality on the purchase intention of online store users in Batam City. The results of direct and partial marketing research on product quality affect the purchase intention of online store applications.